The Influence Of Influencer Marketing Rafi Ahmad On The Interest In Buying Erigo Products On Social Media Instagram On Ums Communication Science Students - Pri Hasdandi Rafli Saputra; Budi Santoso (Penerbit Jurnal Indonesia, 2024)
The purpose of this study was to analyze the effect of influencer marketing Rafi Ahmad on buying interest in Erigo products on Instagram social media for UMS Communication Science students. This research method is quantitative. Researchers used a survey method with a questionnaire that was conducted online via google forms. In this study, the population determined was Rafi Ahmad's Instagram followers in 2023, which amounted to 71,200,000 followers. Researchers used non-probability sampling techniques, with purposive sampling techniques. The data collection technique in this study used a questionnaire and research instruments. Data analysis methods with the help of the SPSS program to prove the relationship and influence between the research variables, by conducting data tests. The results of this study are that using the SOR theory framework, the influence of influencer marketing Rafi Ahmad on buying interest in Erigo products on Instagram social media has a positive and significant effect so that it can be explained Stimulus: Interesting promotional content and positive interaction between Rafi Ahmad and his followers on Instagram. Organism: Followers respond to the content with a sense of connection to Rafi Ahmad, trust in his recommendations, and interest in the lifestyle displayed. Response: Followers show increased purchase intention towards Erigo products, reflected in purchase actions, search for more information, and engagement with the brand within the Instagram platform. Thus, the SOR theory provides a comprehensive view of how influencer marketing can affect product purchase intention on Instagram social media through the process of stimulus, organism, and response.